Der deutsche Krieg im Osten 1941-1944 Facetten einer Grenzüberschreitung - Hartmann, Christian 1959- (R. Oldenbourg, 2009)
Annotation
Maps on endpapers
Keywords: Geschichte; Guerre mondiale, 1939-1945; Sociologie militaire; Armed Forces; Atrocities; HISTORY; Military campaigns; Russlandfeldzug; Sociology, Military; Sociology, Military -- Germany -- History -- 20th century; World War, 1939-1945 -- Atrocities -- Europe, Eastern; World War, 1939-1945 -- Campaigns -- Eastern Front; Russlandfeldzug -- 1941-1945; 1900-1999; Germany / Armed Forces / History / World War, 1939-1945; Soviet Union / History / German occupation, 1941-1944; URSS / Histoire / 1941-1944 (Occupation allemande); Eastern Europe; Eastern Front (World War (1939-1945)); Germany; Soviet Union; Aufsatzsammlung; Electronic books; History